2021
DOI: 10.1055/s-0041-1722881
|View full text |Cite
|
Sign up to set email alerts
|

TSC1 as a Novel Gene for Sleep-Related Hypermotor Epilepsy: A Child with a Mild Phenotype of Tuberous Sclerosis

Abstract: Sleep-related hypermotor epilepsy (SHE) is a rare syndrome that presents with hyperkinetic asymmetric tonic/dystonic seizures with vegetative signs, vocalization, and emotional facial expression, mainly during light non-rapid eye movement sleep stages. The role of various genes (CHRNA4, CHRNB2, CHRNA2, KCNT1, DEPDC5, NPRL2, NPRL3, and PRIMA1) has previously been reported, though genetic etiology is assessed in less than 10% of cases. We report the case of a 5-year-old female carrying the TSC1 variant c.843del … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…42 A case report suggests that SHE may also be associated with mutations in the TSC1 gene, which plays a pathogenic role in SHE through the (mTOR) pathway. 43 Recent studies in epileptic brain tissues have suggested that defective expression of circadian locomotor output cycles kaput (CLOCK), a transcription factor that regulates the circadian rhythm and mTOR pathway, may be responsible for the predisposition of epileptic seizures during sleep. 44 The genetic and structural etiologies of SHE are not mutually exclusive.…”
mentioning
confidence: 99%
“…42 A case report suggests that SHE may also be associated with mutations in the TSC1 gene, which plays a pathogenic role in SHE through the (mTOR) pathway. 43 Recent studies in epileptic brain tissues have suggested that defective expression of circadian locomotor output cycles kaput (CLOCK), a transcription factor that regulates the circadian rhythm and mTOR pathway, may be responsible for the predisposition of epileptic seizures during sleep. 44 The genetic and structural etiologies of SHE are not mutually exclusive.…”
mentioning
confidence: 99%
“…Referencing other mTOR-pathway-related epilepsies, TS-related seizures are also noted to be carbamazepine-responsive with one large study demonstrating 55 % of TS patients were seizure-free on carbamazepine [13] . Another case-report describes carbamazepine-responsiveness in TSC1-associated SHE [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers detected the TSC1 gene mutation Ser282GInfs*36; however, despite negative paternal gene mutation test results, they were unable to determine whether the mutation was hereditary since the patient's mother was deceased. Notably, the patient's maternal aunt had a history of generalized epilepsy (26). The Ser282GInfs*36 mutation detected in TSC1 and the Arg905GIn mutation detected in TSC2 are both pathogenic variants (19,26).…”
Section: Tsc Complex-related Genesmentioning
confidence: 96%
“…Notably, the patient's maternal aunt had a history of generalized epilepsy (26). The Ser282GInfs*36 mutation detected in TSC1 and the Arg905GIn mutation detected in TSC2 are both pathogenic variants (19,26). Patients with the Ser282GInfs*36 mutation exhibited structural damage in the cerebral cortex but had a good response to medication, whereas patients with the Arg905GIn mutation did not show structural damage in the cerebral cortex but presented with refractory epilepsy.…”
Section: Tsc Complex-related Genesmentioning
confidence: 99%